2020
DOI: 10.3390/ijms21031101
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of Mitochondrial Substrate Flux in a Mouse Model of Nonalcoholic Fatty Liver Disease

Abstract: Maladaptation of mitochondrial oxidative flux seems to be a considerable feature of nonalcoholic fatty liver disease (NAFLD). The aim of this work was to induce NAFLD in mice fed a Western-style diet (WD) and to evaluate liver mitochondrial functions. Experiments were performed on male C57BL/6J mice fed with a control diet or a WD for 24 weeks. Histological changes in liver and adipose tissue as well as hepatic expression of fibrotic and inflammatory genes and proteins were evaluated. The mitochondrial respira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Significant reduction of basal levels of liver GSH has been reported in NAFLD, either in patients [ 101 , 102 ] or in some rodent models [ 103 , 104 ]. However, other animal investigations did not find any significant decrease in hepatic GSH content [ 49 , 50 , 105 , 106 ], although this was sometimes associated with higher levels of oxidized GSH (GSSG) [ 105 ].…”
Section: Factors Modulating Apap Hepatotoxicity In Obesity and Nafldmentioning
confidence: 99%
“…Significant reduction of basal levels of liver GSH has been reported in NAFLD, either in patients [ 101 , 102 ] or in some rodent models [ 103 , 104 ]. However, other animal investigations did not find any significant decrease in hepatic GSH content [ 49 , 50 , 105 , 106 ], although this was sometimes associated with higher levels of oxidized GSH (GSSG) [ 105 ].…”
Section: Factors Modulating Apap Hepatotoxicity In Obesity and Nafldmentioning
confidence: 99%
“…89 Mice fed with a "Western" diet for 24 weeks developed liver steatosis with decreased mitochondrial respiration but no changes in FA β-oxidation and no traces of ROS, suggesting that mitochondria adapted to the excess substrate. 83 Mice fed for 16 weeks with three different hypercaloric diets HF, high sucrose or HF-high sucrose diet presented hepatic steatosis regardless of no changes in mitochondrial oxidative capacity, FA β-oxidation or ROS production. 90 The discrepancy in the results may be linked to the different animal models and the different stages of the disease of human subjects.…”
Section: Dysfunction Responsible For Progression From Nafl To Nash?mentioning
confidence: 96%
“…72 Recently, it was reported that high fat-fed animals have decreased mitochondrial respiration with succinate, but no change in FA oxidation. 83 Some reports showed that mitochondrial respiration decreases during NASH development, 73,77 with reduced synthesis of ATP. [84][85][86][87] Others have shown that despite impairment in lipids or glucose metabolism, NAFL/NASH mitochondria were not dysfunctional.…”
Section: Dysfunction Responsible For Progression From Nafl To Nash?mentioning
confidence: 99%
“…Having established that FFA stimulates mitochondrial respiration in HepaRG cells, but not in HepG2 cells, the present study then investigated which pathway leading into the Q-junction may be responsible for causing these outcomes. Our previously published studies on mouse models of NASH revealed a decreased complex II-driven respiration (38,39). Therefore, the present study evaluated OXPHOS, MRc and LEAK respiration in the presence of complex I-driven respiration substrates [pyruvate/malate and glutamate/malate (Fig.…”
Section: Ffas Increase Complex I and Ii-driven Respiration And β-Oxid...mentioning
confidence: 98%